2016
DOI: 10.1080/01612840.2016.1189636
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Web-Based Training Program for Professional Carers Working With People With Learning Disabilities and Challenging Behavior: A Pilot Study with SSED-Design

Abstract: The interaction between people with intellectual disabilities and professional carers is often influenced by communicative difficulties contributing challenging behaviours. The aims of this study were to evaluate to a web-based training program aimed at improving carers' abilities to interact with people with learning disabilities who exhibit challenging behaviours and to explore carers' experiences of participating in such a program. A single-subject experimental design and mixed methods were used to integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Our results are consistent with prior research that have shown that IWT may be an effective strategy to teach intervention skills to individuals working or living with persons with developmental disability (Antonsson et al, 2016, Nosik, Williams, Garrido, & Lee, 2013Eldevik et al, 2013;Gerencser et al 2017;Pollard et al, 2014). Our study is the first to show that IWT can also be adapted to teach function identification and intervention selection to parents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with prior research that have shown that IWT may be an effective strategy to teach intervention skills to individuals working or living with persons with developmental disability (Antonsson et al, 2016, Nosik, Williams, Garrido, & Lee, 2013Eldevik et al, 2013;Gerencser et al 2017;Pollard et al, 2014). Our study is the first to show that IWT can also be adapted to teach function identification and intervention selection to parents.…”
Section: Discussionsupporting
confidence: 91%
“…One promising solution is to train parents to reduce challenging behaviour using interactive web-based training (IWT), which combines the use of self-paced computer instruction (e.g., oral explanations, descriptive slides, self-guided practice, integrated quizzes) and video models (Antonsson, Graneheim, Isaksson, Åström, & Lundström, 2016;Gerencser, Higbee, Akers, & Contreras, 2017;Pollard, Higbee, Akers, & Brodhead, 2014). To this end, we recently developed an IWT designed to support parents in the reduction of challenging behaviour in children with developmental disability.…”
Section: Using Interactive Web Training To Teach Parents To Select Fumentioning
confidence: 99%
“…Several studies referred to knowledge as an essential factor in building staff–client interactions. Besides knowledge about the nature of a treatment programme (Knotter et al, 2018), knowledge mainly referred to gaining personal knowledge about a specific client and getting to know and understand the client by establishing personal relationships (Antonsson et al, 2008, 2013, 2016; Bambara et al, 2001; Bradshaw & Goldbart, 2013; Ravoux et al, 2012; Whittington & Burns, 2005). Personal relationships were facilitated by spending time together (Antonsson et al, 2013; Bambara et al, 2001; Bradshaw & Goldbart, 2013), knowing a clients’ life history and daily life experiences (Antonsson et al, 2008, 2013; Knotter et al, 2018), and to some degree by talking to or observing others interact with the client (Bradshaw & Goldbart, 2013; Ravoux et al, 2012; Whittington & Burns, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Confidence appeared to be another important factor in meaningful interactions (Antonsson et al, 2016; Nagra et al, 2017; Ravoux et al, 2012; Thompson et al, 2019). Willems et al (2016) showed the positive effect of self‐efficacy (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A lifelong learning approach is thus central to the nursing professional practice (EU, ). Web‐based learning can be one answer for keeping nurses’ knowledge updated within the flexible schedule required in health care as it allows self‐regulatory learning (Antonsson, Graneheim, Isaksson, Åström, & Lundström, ). Web‐based learning is rapidly increasing (Chiu & Tsai, ) with advantages in healthcare learning in terms of accessibility, flexibility and cost‐effectiveness (Smith, ; Ward, Stevens, Brentnall, & Briddon, ).…”
Section: Introductionmentioning
confidence: 99%